2012
DOI: 10.1186/gb-2012-13-10-r97
|View full text |Cite
|
Sign up to set email alerts
|

Aging effects on DNA methylation modules in human brain and blood tissue

Abstract: BackgroundSeveral recent studies reported aging effects on DNA methylation levels of individual CpG dinucleotides. But it is not yet known whether aging-related consensus modules, in the form of clusters of correlated CpG markers, can be found that are present in multiple human tissues. Such a module could facilitate the understanding of aging effects on multiple tissues.ResultsWe therefore employed weighted correlation network analysis of 2,442 Illumina DNA methylation arrays from brain and blood tissues, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

35
538
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 583 publications
(578 citation statements)
references
References 52 publications
(96 reference statements)
35
538
2
3
Order By: Relevance
“…From adulthood to advanced age, overall levels of DNA methylation remain stable in blood, while interindividual variability increases over that time (Talens et al ., 2012; Weidner et al ., 2014). Postadulthood, many studies have found a mean decrease in blood DNA methylation with increasing age (Bjornsson et al ., 2004; Boks et al ., 2009; Heyn et al ., 2012; Horvath et al ., 2012; Hannum et al ., 2013; Johansson et al ., 2013; Florath et al ., 2014; Weidner et al ., 2014). These changes are less likely to occur in promoters and more likely to be observed in enhancers (Johansson et al ., 2013).…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
See 4 more Smart Citations
“…From adulthood to advanced age, overall levels of DNA methylation remain stable in blood, while interindividual variability increases over that time (Talens et al ., 2012; Weidner et al ., 2014). Postadulthood, many studies have found a mean decrease in blood DNA methylation with increasing age (Bjornsson et al ., 2004; Boks et al ., 2009; Heyn et al ., 2012; Horvath et al ., 2012; Hannum et al ., 2013; Johansson et al ., 2013; Florath et al ., 2014; Weidner et al ., 2014). These changes are less likely to occur in promoters and more likely to be observed in enhancers (Johansson et al ., 2013).…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
“…These changes are less likely to occur in promoters and more likely to be observed in enhancers (Johansson et al ., 2013). Regions that gain DNA methylation with age are enriched for CpG islands, while nonislands tend to lose DNA methylation with age (Rakyan et al ., 2010; Heyn et al ., 2012; Horvath et al ., 2012; Florath et al ., 2014; Weidner et al ., 2014). …”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
See 3 more Smart Citations